Open hepatic artery aneurysm in bile ducts - Praderi, Raúl C; Curuchet, Eduardo; Armand Ugon, César (Cirugía del Uruguay, 2020)
A case of aneurysm of the right hepatic artery surviving after surgery is reported upon. Ligation and obliterating endoaneurysmorrhaphy were carried out. The common duct was reconstructed upon a Kehr tube. The classification of post-traumatic ane rsms is discussed, a difference being ' ablisbed with the intra and extra-hepa. ·e arteriobiliary fistulas with hemobilia. he main differential diagnostic featu: es, as regareis a jaundice with digestive nemorrhage and pain, are pointed out. A survey is carried out of 19 similar cases reported in the literature, the pertient surgical procedures being dealt with.